Integral constraints pursuit problem for 3-system of differential equations in hilbert space / Diviekga Nair Madhavan ...[et al.] - Madhavan, Diviekga Nair; Alias, Idham Arif; Ibragimov, Gafurjan; Mat Hasim, Risman (Universiti Teknologi MARA, Kelantan, 2023)
This paper investigates a pursuit game of an infinite 3-system of differential equations involving one pursuer and one evader. Integral constraints are imposed on the players' control parameters where the resource of the pursuer is greater than that of the evader. The aim of the pursuer is to bring the initial state ξ0 of the system into another non-zero state ξ1 of the system at some time on a finite time interval to complete the pursuit. We constructed a control function needed in solving control problems of the system and developed an admissible pursuer's strategy to solve the pursuit problem. Pursuit is shown to be completed in the game as the state of the system reaches state ξ1 at a finite time θ > 0.